Factors affecting exclusive breastfeeding of primiparous mothers: scoping review - Hairiana Kusvitasari; Ismarwati Ismarwati; Nurul Mahmudah (Universitas 'Aisyiyah Yogyakarta, 2022)
Primiparous mother's breastfeeding practice in developed and developing countries is influenced by various factors, such as sociodemographic, socio-cultural and health factors. Primiparous mother's experience of stopping breastfeeding is related to the mother's lack of knowledge about breastfeeding, breastfeeding skills, and the initial painful experience of breastfeeding. The objective of the scoping review is to review the evidence of the factors that influence exclusive breastfeeding in primiparous mothers. This scoping review used the Arksey and O'Malley framework. Identification of relevant studies from 2009-2019 used 5 databases. Data based are PubMed, Sciendirect, Ebsco, Wiley and Proquest. The results of this scoping review consisted of 8 articles out of 421 articles and were rated. Found 2 themes, which were internal factors and external factors. The most influential internal factor is the psychological factor of primiparous mothers, when the mother feels stressed, the mother can decide to stop breastfeeding and switch to giving formula milk to her baby and external factor is socio-cultural. There are still many countries that adhere to socio-cultural practices that can hinder the process of exclusive breastfeeding.